RANCANG BANGUN SISTEM PEMANTAUAN KUALITAS UDARA MENGGUNAKAN WIRELESS SENSOR NETWORKS DENGAN TOPOLOGI CLUSTER - Saraswati, Dyah Lestari; Jusak, Jusak; Triwidyastuti, Yosefine (Journal of Control and Network Systems (JCONES), 2016)
It is commonly understood that air pollution brinqs detrimental effect to human health, it can cause diseases and lead todeath. Therefore, it is urgently required to monitor airborne levels continously. In this research, it monitoring system utilizing the wireless sensor networks with cluster method. We consider that there are two clusters where every cluster head has two child nodes equipped with a CO sensor and a CO2 sensor for each node. Data from child node sent to server through parent node and each cluster head. We used the xbee radio as wireless transmision from child node to parent node, we used the wifi Tonylabs CC3000 module as wireless transmission from parent to server.The result shows that delay and packet loss between child node and parent node through the xbee are aproximately 4,75 seconds and 5%, respectively. This means that the system has short delay and relatively low packet loss. On the other had the packet loss from parent node to server are relative higher than that from the child node to parent node i.e. aproximately 14,17 %, Interestingly it can achievedelay of close to zero second during transmission.